Toxicological and therapeutic evaluation of the algae Macrocystis pyrifera (Phaeophyceae) in rodents - Tapia-Martínez, Jorge; Cano-Europa, Edgar; Casas-Valdez, Margarita; Blas-Valdivia, Vanessa; Franco-Colin, Margarita (Revista de Biología Marina y Oceanografía, 2020)
Macrocystis pyrifera is a giant brown seaweed with high nutritional content, used as a dietary supplement in some farm animals. It contains fucoidan which has a pharmacological effect on lipids and glucose metabolism. Some brown seaweeds can bioaccumulate toxic elements in their cell wall, representing a problem if toxicity tests that guarantee the safety of their consumption are not done. M. pyrifera, does not present toxicological studies that guarantee its safety. This work aimed to perform the acute and subchronic toxicological evaluation of M. pyrifera in rodents as well as to determine its possible therapeutic effect. Fronds of M. pyrifera were collected in Baja California Sur, Mexico, for drying and obtaining algae flour. The acute toxicity test LD50 was performed in C57BL / 6 male mice (25 ± 3 g) for 7 days, finding an LD50 greater than 10 g kg-1. Subchronic toxicity was determined for 121 days in adult male Sprague Dawley rats (98 ± 2 g), during which the experimental animals showed no signs of toxicity, or changes in the hematological, biochemical and histopathological parameters of the organs. The reactive oxygen species, lipid peroxidation or glutathione ratio were not different from the control group. A therapeutic effect on the regulation of body weight and a hypolipidemic effect (triacylglycerides: 82.27 ± 5.55 mg dl-1, cholesterol: 98.61 ± 6.48 mg dl-1) were found. It is concluded that, under the conditions in which this study was developed, the consumption of M. pyrifera as a functional ingredient is safe.